2007
DOI: 10.1038/sj.bjc.6603631
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between subcellular localisation of Foscan® and caspase activation in photosensitised MCF-7 cells

Abstract: The present study investigates the relationship between the subcellular localisation of Foscan s and intrinsic apoptotic pathway post Foscan s -based photodynamic therapy (PDT). With this purpose, mammary carcinoma MCF-7 cells were incubated with Foscan s for 3 or 24 h and then subjected to equitoxic light doses. Fluorescence microscopy revealed very good Foscan s co-localization to endoplasmic reticulum (ER) and Golgi apparatus after 3 h incubation with MCF-7 cells. Progressive increase in incubation time sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 34 publications
(43 reference statements)
4
48
0
2
Order By: Relevance
“…It had been reported that apoptotic pathways may be initiated [9][10][11][12], however, autophagy or necrosis [13] may prevail -especially if high PDT doses are applied [14].…”
Section: Introductionmentioning
confidence: 99%
“…It had been reported that apoptotic pathways may be initiated [9][10][11][12], however, autophagy or necrosis [13] may prevail -especially if high PDT doses are applied [14].…”
Section: Introductionmentioning
confidence: 99%
“…For these reason, we applied them to verify the sensitivity and reliability of our luciferase reporter. Marchal et al (2007) proved a predominant accumulation of Foscan® in the ER after 24 h incubation. The reporter cells were treated by PDT under a specific light fluency (7.2 J/cm 2 ) with various positive compounds concentration (Me, 0∼10 μM; Foscan®, 0∼12 μM) after 24 h incubation.…”
Section: Resultsmentioning
confidence: 99%
“…It is widely reported that human breast cancer cell line MCF-7 is sensitive to ER-targeting PDT (Marchal et al 2007;Li et al 2010;Xue et al 2001). So this study applied MCF-7 as model cell.…”
Section: Introductionmentioning
confidence: 99%
“…29 When such a mechanism does not remedy the excessive oxidative stress, the "unfolded protein response" will activate the caspase cascade, resulting in apoptosis. 30 While numerous in vitro studies have been done to characterize the photodynamic activities of different photosensitizers, relatively little is known about their efficacy in the animal model.…”
Section: Discussionmentioning
confidence: 99%